A Rare Cause of the Cough: Primary Small Cell Carcinoma of Esophagus—Case Report - Erdal Yekeler; Timur Koca; Semra Vural (Case Reports in Medicine)
Primary small cell carcinoma of the esophagus is a relatively rare malignancy. It is highly progressive and poorly prognostic in untreated conditions. In the western populations, the rate of primary small cell carcinoma in all esophageal cancer types is between 0.05% and 2.4%, while it is endemically increasing up to 7.6% in the eastern populations. Most of the cases are in extensive stage at the time of diagnosis. Surgery is the treatment of choice in limited stages, but treatment must be multimodal in primary small cell carcinoma of the esophagus. A 47-year-old woman was referred to our clinic with gradually increasing severe dry cough and slight difficulty in swallowing for 20 days. Chest X-ray graphy was normal, and computed tomography of the chest showed multiple mediastinal lymph nodes and hepatic metastases. Her endoscopic examination revealed an endoluminal vegetative mass between 20 cm and 23 cm of her esophagus. The case was reported as small cell carcinoma of the esophagus on histopathological examination. The case was assumed inoperable, and chemotherapy and radiotherapy were planned. We presented a rare cause of the cough and primary esophageal small cell carcinoma in this paper.